ANALISIS HASIL BELAJAR MELALUI PENGGUNAAN MEDIA VIDEO DI SEKOLAH DASAR - Haqqi, Muttahid; Arrahim (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
The aim of this study is to explore the learning outcomes achieved by students through the implementation of video media in science lessons at elementary schools, using the Systematic Literature Review (SLR) method. This method was chosen to ensure a structured and organized data collection process. Data were collected through a search of published scholarly articles, with a focus on articles released in the past year (2024). In this study, 15 articles were analyzed to obtain relevant information. This literature review provides valuable insights into how video media can contribute to student learning outcomes, considering various involved indicators. Based on the analysis of existing literature, student learning outcomes are determined by several aspects. The cognitive aspect includes understanding and applying concepts, the affective aspect relates to students' attitudes and motivation, while the psychomotor aspect focuses on the practical skills acquired by students. The results of this study provide significant recommendations, emphasizing the importance of integrating video media into the learning process. The use of video media can enhance student engagement and facilitate better understanding of science material. Therefore, the implementation of video media in elementary school education is expected to maximize student learning outcomes and support their overall academic development.